PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Ani Laila; Yessi Novita; Yan Sartika; Ari Susanti (LPPM Universitas Abdurrab, 2021)
Cesarean section gives effects to the mother, including post-surgical pain. The pain cause physical and psychological reactions for the postpartum mother such as impaired mobilization, lazy activity, sleeplessness, loss of appetite, and lack of care for the baby. To overcome this, there are need for a way to control pain with non-pharmacological therapy, one of which is handheld finger relaxation technique. The purpose of this study was to determine the effect of handheld relaxation technique on the intensity of pain in post-cesarean section patients in Camar I Room of Arifin Achmad Hospital in Riau Province. This pre-experimental study used one group pretest-posttest design. This study was conducted from March to June 2018. The population was all post-cesarean section mothers with a sample of 20 people. Data were analyzed using the Wilcoxon test. The result showed that the mean pain intensity before handheld relaxation techniques was 6.05 while after was 1.50. The result was affects of handheld relaxation techniques on the intensity of pain in this study with a p value of 0.000 (Î± <0.05). The results of this research can be used as a method for reducing pain in post-cesarean section patients at Arifin Achmad Hospital in Riau Province.